Tetramethylpyrazine Improves Cognitive Function of Alzheimer’s Disease Mice by Regulating SSTR4 Ubiquitination - Weng G; Zhou B; Liu T; Huang Z; Huang S (Dove Medical Press, 2021)
Guohu Weng,1 Bo Zhou,2 Tao Liu,3 Zhengxin Huang,2 Shixiong Huang3 1Department of Encephalopathy, Hainan Provincial Hospital of Traditional Chinese Medicine, Haikou, 570203, Hainan, People’s Republic of China; 2Department of Cardiology, Hainan Provincial Hospital of Traditional Chinese Medicine, Haikou, 570203, Hainan, People’s Republic of China; 3Department of Neurology, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, Haikou, 570311, Hainan, People’s Republic of ChinaCorrespondence: Shixiong HuangDepartment of Neurology, Hainan General Hospital, Hainan Affiliated Hospital of Hainan Medical University, No. 19 Xiuhua Road, Xiuying District, Haikou, 570311, Hainan, People’s Republic of ChinaTel/Fax +86-0898-68642129Email huangsx0813@163.comPurpose: Many researches have investigated the functions of tetramethylpyrazine (TMP) in Alzheimer’s disease (AD). This study aimed to discuss the underlying mechanism of TMP in AD mice.Methods: TMP (200 mg/kg) was administered to 6-month-old APP/PS1 transgenic mice, and behavioral changes and hippocampal nerve injury in AD mice were detected. Apoptosis and autophagy-related protein levels were detected. Changes in gene expression before and after TMP treatment were compared using transcriptome sequencing. The effects of Cullin 4B (CUL4B) overexpression and somatostatin receptor 4 (SSTR4) silencing on AD symptoms and SSTR4 ubiquitination in APP/PS1 mice were observed. SH-SY5Y and PC12 cells were treated with 25 μmol/L Aβ25– 35 and TMP to observe cell viability, apoptosis, and autophagy. Cell viability and apoptosis were measured again after treatment with proteasome inhibitor MG132 or lysosomal inhibitor 3-mA.Results: TMP treatment improved the behavioral cognition of APP/PS1 mice and improved the neuronal apoptosis and damage in brain tissue. CUL4B was significantly upregulated in APP/PS1 mouse brain tissue, and SSRT4 protein was downregulated, and the levels of CUL4B and SSRT4 were negatively correlated. TMP treatment downregulated CUL4B, inhibited SSRT4 ubiquitination and upregulated SSRT4 protein level in APP/PS1 mouse brain tissue, while CUL4B overexpression or SSRT4 silencing reversed the effect of TMP. TMP and MG132 improved the decreased activity, increased apoptosis and increased SSRT4 protein in SH-SY5Y and PC12 cells treated with Aβ25– 35, but not 3-mA. CUL4B overexpression promoted the ubiquitination of SSTR4 in cells, which partially reversed the effect of TMP.Conclusion: TMP could improve the cognitive ability of AD mice by inhibiting CUL4B expression and the ubiquitination degradation of SSTR, and alleviating neuronal apoptosis and injury. This study may offer a new therapeutic option for AD treatment.Keywords: Alzheimer disease, tetramethylpyrazine, somatostatin receptor 4, ubiquitination, Cullin 4B